Life on the ice-edge: Paleoenvironmental significance of the radiolarian species Amphimelissa setosa in the northern hemisphere. (15th November 2020) - Hernández-Almeida, Iván; Bjørklund, K.R.; Diz, P.; Kruglikova, S.; Ikenoue, T.; Matul, A.; Saavedra-Pellitero, M.; Swanberg, N.
Abstract: The high-latitude Northern Hemisphere is a key region in the global climate balance. Variations in sea-ice extent affect biological productivity, CO2 exchange and carbon drawdown. Marine proxies indicative of proximity of the ice-marginal zone are therefore essential to understand these processes. Amphimelissa setosa is nowadays a dominant radiolarian species in the Arctic basin and very abundant in the high-latitude North Atlantic. This species, now absent from the North Pacific, has been widely used as a qualitative proxy of modern and past environmental conditions in the high-latitude Northern Hemisphere. Using our new and published data on the distribution of A. setosa in plankton, sediment trap, surface sediment and downcore samples, we provide a quantitative ecological context for the occurrence of this species. We find that the optimal depth and season of A. setosa in the modern North Atlantic and the Chukchi Sea are 160 m and the late boreal summer/early fall (August–October), respectively. A regression model combining environmental variables (temperature, salinity, silicate and chlorophyll- a concentrations, apparent oxygen utilization, sea-ice) at that season and depth, are able to explain 43% of the distribution of this species in surface sediments. Based on these new findings, we conclude that the presence of A. setosa in surface sediments is closely related to high primary production in the proximity of the sea-ice and areas of ice rafting. The onset of this species started at ca. 1.5 Ma in the North Pacific, linked to a gradual cooling, increased silica availability and southward advance of the ice-margins since the Early Pleistocene. Amphimelissa setosa 's decline in this region was likely caused by the development of a quasi-permanent halocline, perennial sea-ice and depletion of silica during marine isotope stage 4. In the high-latitude North Atlantic, the relative abundance of A. setosa appears to be related to cooling and supply of dissolved silica from the continent during ice-rafting events. The comprehensive approach taken in this study suggest that A. setosa is a useful proxy to explore past variations in the ice-cover in the high-latitude Northern Hemisphere. Highlights: We discuss modern and fossil significance of the radiolarian Amphimelissa setosa. A. setosa is a new proxy for near ice-edge conditions. Onset of A. setosa in the N Pacific (1.5 Ma) linked to sea-ice southward expansion. Disappearance in the N Pacific (MIS 4) driven by Si deprivation and halocline changes.